Implementation of Brainstorming Learning Method to Improve Students' Understanding of the Material of Hadith Elements for Class X Madrasah Aliyah Negeri 2 Jepara - Liana Fika Ariyani; Darnoto (al-Iltizam: Jurnal Pendidikan Agama Islam, 2025)
The purpose of this study was to test the brainstorming method in learning and improving the understanding of tenth grade students of MAN 2 Jepara Language on the material of hadith elements. The main challenge of this study is that students have difficulty understanding complex hadith material that is relevant to everyday life, not only that, students' public speaking skills are also still lacking. The brainstorming method is believed to be able to improve students' understanding and motivation to learn and improve public speaking, because it encourages their active participation in discussions to express opinions, generate ideas, and relate the material to personal experiences. In this study, the researcher conducted a study using the classroom action research (CAR) methodology using the initial test instrument, namely the pre-test and ending with a comprehensive post-test (quasi-experiment). The researcher selected a sample using the purposive sampling technique, which was studied was class X Language MAN 2 Jepara. Using the statistical t test (difference test) using SPSS 23.0 software in analyzing the data. The results showed that there was an increase in the average value of the pre-test and post-test from 61.8519 to 76.8519. The implementation of the brainstorming learning method has proven effective in improving student understanding based on pre-test and post-test scores.